Risk management in diffused structures: Analysis for Shared Services Centers - Zaporowska, Zuzanna; Szczepański, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Research background: Shared Services Centers (SSCs) are often a spin-off of corporate services to separate all operational tasks from the corporate headquarters. The primary focus of the head-quarters should be on leadership and corporate governance. However, many SSCs have also been given some corporate functions. Risk management is a significant part of governance and one of its principles. The effectiveness of risk management depends on its integration into the organization’s governance, including decision-making. The question is how a modern SSC manages this part of governance. Purpose: This study aims to present the conditions that prove the implementation of risk management in SSCs and to evaluate the most effective risk management model. Research methodology: Targeted literature review followed by surveys and a case study. Results: The risk management process consists of several stages that are repeated in many models (identification and risk assessment, risk management model selection, and monitoring). Thus, it is possible to use each model in the SSC concerning the migrated processes, considering the limitations of the strategic goals definition. However, not all methods will find a potential application in risk management in the SSC, considering the most effective risk assessment. Novelty: While the literature provides models that can be of use, a lack of specific guidelines has been recognized, especially regarding the risk management aspect in SSCs. In the last decade, the focus was on the expected benefits coming from standardization, ignoring the new risks in SSC processes.
Keywords: risk management; Shared Services Centers – SSC; Global Business Services – GBS; outsourcing; lean risk management; FERMA; PMBOK; M_o_R; COSO; ISO 31000